2005
DOI: 10.1007/s10909-005-1528-4
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in Superfluids: Effect of Gravity

Abstract: We discuss the influence of an external field on energy transport in superfluid. He-II is not isothermal in presence of Earth gravity; instead, it supports finite temperature gradient given by a Fourier-like equation. We calculate asymptotic behavior of the effective heat resistance in the vicinity of the $\lambda$-transition.Comment: 6 page

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Its origin should be clarified. It is shown in [4] that atoms of He II possess an inertial DM caused by their acceleration in sound waves. However, such DM give polarization which is two to three orders of magnitude smaller than the observed value.…”
Section: Induced Dipole Moment Of He II Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its origin should be clarified. It is shown in [4] that atoms of He II possess an inertial DM caused by their acceleration in sound waves. However, such DM give polarization which is two to three orders of magnitude smaller than the observed value.…”
Section: Induced Dipole Moment Of He II Atomsmentioning
confidence: 99%
“…This is rather unexpected, given that He II is a dielectric and that a free He 4 atom does not possess either dipole or higher multipole moments. Several models have been proposed to explain the electric activity of He II [4][5][6], but each of them encounters with certain difficulties and does not explain the effects of [1][2][3] in a plausible way. In this work, we study a possible nature of the electric activity of He II observed by Rybalko [1] in experiments with second sound.…”
Section: Introductionmentioning
confidence: 99%
“…An observation of electric induction in superfluid 4 He induced by relative motion of its normal and superfluid components has been recently reported [1,2]. This new extraordinary effect was revealed in two different types of experiments: electric potential oscillations were generated by a second-sound wave of which the velocities of normal υ n and superfluid υ s components relate as n s s n ρ ρ υ υ = (here ρ s and ρ n are the densities of the superfluid and normal components, respectively), and by liquid helium motion in a torsion oscillator whose walls affect the normal component only.…”
Section: Introductionmentioning
confidence: 99%
“…A reverse effect (second-sound wave generation by an ac electric field) was also observed. The experimental finding of mechanoelectric effect in He II has stimulated a number of theoretical studies aiming to explain its mechanism [3][4][5][6][7][8]. On the basis of experiments [1,2], it could be assumed that the relative motion of the normal and superfluid components is a result of internal electromagnetic forces related to the macroscopic quantum ordering.…”
Section: Introductionmentioning
confidence: 99%